Development of Pop Up Book Media to Teach Reading Skills for Tenth Grade Students At SMK Annur Bululawang - Surwanto, Danu (English Education Study Program Faculty of Teacher Training and Education, 2024)
This Study aim For developing learning media in the form of pop-up book narrative text and know How to level the feasibility of the media. Research is done on student class 10 SMK An-Nur Bululawang. The method of research used is Research and Development (R&D) which uses the ADDIE model. The stages include (1) Analysis needs, (2) Development product (3) Product design (4) Implementation product (4) Product evaluation. Determination feasibility is carried out with validation expert learning, validation media expert, and validation expert language. After That researcher does testing the product. Research And Development produce pop-up book media that is feasible to use based on a study from (1) Media expert validator get 90% rating (2) Expert validators learning get an evaluation by 90%. Expert validator Language gets evaluation by 85%. Assessment response students get a percentage evaluation of 88% which means the media can be received by the student. Reason choose study This is Because development previously different in place variable And object study as well as No exists Validation expertlanguage.